Psychological effects of the Coronavirus disease-2019 pandemic - Sood, Sadhika (Research and Humanities in Medical Education, 2020)
Going by the current physical reach of the COVID-19 pandemic in the population there are bound to be long-term socio-economic and psychological implications. The swift rise of fear and anxiety among people due to uncertainty of the disease are coupled with essential yet socially disruptive measures like lockdowns and quarantines. These can lead to significant psychological and psychiatric disturbances such as post-traumatic stress disorder, depression, anxiety, panic disorders, and behavioural disorders. Predisposing factors include staying away from family, loneliness, misinformation on social media, financial insecurity and stigmatization. Healthcare workers, too, have a high risk of developing post-traumatic stress disorder and burnout; therefore, it is paramount to understand and research the psychological impact and key determinants to prevent, identify, and manage such problems. Suggested actions include support lines for anxious people, tele-counselling, virtual connecting & help groups, encouraging meditation, conducting research on psychological consequences, and developing and utilising suitable interventions.